A grand multipara woman in the modern era: A case of public health dilemma from an urban slum (Indian Journal of Case Reports, 2024)
With the advancement in family planning practices and shifting norms from “hum do hamare do” to “one child,” there still exist mothers who are delivering their 10th children. Such an example is a woman residing in an urban slum in the Khordha district of Odisha, India. She has never used any modern methods of contraception. Neither the health workers in that area could fulfill her unmet need for family planning. The helpless mother missed all the antenatal checkups as she did not have anyone to accompany her to the hospital. Three of her children were delivered at home and none of them were immunized to date. She has become a victim of domestic violence by her husband, who is addicted to alcohol. She has done two medical terminations of pregnancy due to non-usage of any contraception. Neither she is able to provide herself nor her children sufficient food every day, as she is not able to go to work in her post-partum period. Her alcoholic husband is not able to earn regularly and there is no other family member to support her. There is no Accredited Social Health Activist appointed for that area whom she can rely on. We need to look at what is the cause of such a scenario – Is it poverty, lack of awareness, lack of education, or our health system has failed to achieve universal health coverage.